Minimum structural requirements for inhibitors of the zinc finger protein TRAF6. Issue 16 (15th August 2019) - Radwan, Mohamed O.; Koga, Ryoko; Hida, Tomohiro; Ejima, Tomohiko; Kanemaru, Yosuke; Tateishi, Hiroshi; Okamoto, Yoshinari; Inoue, Jun-ichiro; Fujita, Mikako; Otsuka, Masami
Graphical abstract: Abstract: Zinc fingers have rarely been regarded as drug targets. On the contrary, the zinc-binding site of enzymes has often been considered a target of inhibitors. We previously developed a dithiol compound called SN-1 that binds to the zinc finger protein tumor necrosis factor receptor-associated factor 6 (TRAF6) and suppresses downstream nuclear factor-κB (NF-κB) signaling. To determine the minimal structure requirements of TRAF6 inhibitors based on SN-1, NF-κB inhibitory activity and cytotoxicity of its derivatives including new compounds were examined. SN-2, an oxidative type of prodrug of SN-1 with 2-nitrophenylthio groups via disulfide, has the minimum structure for an inhibitor of TRAF6, as seen with cellular experiments. The importance of two side chains with a thiol group was shown with molecular modelling. This study may lead to development of selective TRAF6 inhibitors in the near future.